Pengaruh Literasi Keuangan Syariah dan Pengelolaan Keuangan terhadap Keberlanjutan Usaha Mikro, Kecil, dan Menengah (UMKM) - Risma Wati; Vani Vauliyanti; Yuliyanti (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting economic growth and employment in Indonesia. Nevertheless, many MSME actors continue to encounter challenges related to limited Islamic financial literacy and inadequate financial management practices, which may affect long-term business sustainability. Strengthening financial knowledge based on Islamic principles and improving financial management capabilities are increasingly important in enhancing business resilience and competitiveness. This research investigates the influence of Islamic financial literacy and financial management on the sustainability of MSMEs in Kramatwatu District, Serang Regency. A quantitative approach was employed using primary data collected through questionnaires distributed to 55 MSME owners selected through purposive sampling. Data were analyzed using descriptive statistics, validity and reliability testing, classical assumption testing, and multiple linear regression with the assistance of EViews software. The findings indicate that Islamic financial literacy has a positive and significant effect on business sustainability. Financial management also demonstrates a positive and significant influence on business sustainability. Simultaneously, both variables contribute significantly to the sustainability of MSMEs, indicating that stronger financial understanding and better financial management practices support the continuity and development of business activities. The novelty of this research lies in integrating Islamic financial literacy and financial management perspectives within the context of MSME sustainability at the local level. These findings provide practical implications for policymakers, financial institutions, and MSME development programs in promoting sustainable business growth based on Islamic financial principles.